A Passive UHF RF Identification CMOS Tag IC Using Ferroelectric RAM in 0.35-μm Technology. - Nakamoto, H.
A passive UHF RF identification (RFID) tag IC with embedded 2-KB ferroelectric RAM (FeRAM) for rewritable applications enables a 2.9 times faster read-and-write transaction time over EEPROM-based tag ICs. The resulting FeRAM-based tag has a nominally identical communication range for both read and write operations, which is indispensable for data write applications. The evaluated tag communication range with a folded dipole antenna is from 0 m to 4.3 m, at the 953-MHz carrier frequency with 4-W transmitting Effective Isotropic Radiated Power (EIRP) from a reader/writer. The developed tag IC features two circuit blocks to maximize the communication range in 0.35-mum CMOS/FeRAM technology. First is a CMOS-only full-wave rectifier, which can improve the measured efficiency by up to 36.6% by reducing the input parasitic capacitances and optimization of multiplier structure. This efficiency is more than twice that of previously-published results. Second is a low-voltage current-mode ASK demodulator to accommodate a low-breakdown voltage of FeRAM, which converts the ASK power modulation into a linearly modulated current over an incoming power range of 27 dB, corresponding to the entire communication range. The developed demodulator can thus resolve the primary design tradeoff issue between device protection and detection sensitivity in the conventional voltage-mode demodulator
Keywords: 0.35 micron; 2 kBytes; 4 W; 953 MHz; ASK power modulation; CMOS-only full-wave rectifier; FeRAM-based tag; Effective isotropic radiated power; Electromagnetic radiative interference; Ferroelectric RAM; Ferroelectric random access memories; Folded dipole antenna; Low-voltage current-mode ASK demodulator; Multiplier structure; Parasitic capacitances; Passive UHF RF identification CMOS tag IC; Read-and-write transaction time; Rewritable applications; Voltage-mode demodulator